VALUATION OF KUJANG 1A PLANT USING DISCOUNTED CASH FLOW - Risdiana, Dian
Pupuk Kujang is a subsidiary of Pupuk Indonesia Holding Company (Persero), its main business activities are in the field of fertilizer and petrochemical derivatives. Pupuk Kujang has a dual function, which is to distribute subsidized fertilizer through Public Service Obligation (PSO), and also sell non-subsidized products. The company's revenue is mostly derived from subsidized fertilizers, but there is a government plan to change the subsidy policy from indirect subsidies through fertilizer producers to direct subsidies to farmers, this makes companies must be able to compete in non-subsidized fertilizers market. The problem faced by Pupuk Kujang in competing in the non-subsidized market is the high cost of production, one of which is due to an old and inefficient factory, namely the K1A Plant.